The Synthesis and Characterization of a Novel Ternary Polymer Bisphenol A-4,4’-Difluorobenzophenone-bis(p-hydroxylphenyl)-1,4,5,8-naphthalenetetracarboxylic Diimide Monomer - Dou, Zhiyu; Li, Xianfeng; Zhong, Shuangling; Zhao, Chengji (Polymer bulletin (Berlin, Germany), 2006)
SummaryA novel bis(p-hydroxylphenyl)-1,4,5,8-naphthalenetetracarboxylic diimide (NTDA–OH) monomer was prepared through the condensations of 1,4,5,8-naphthalenetetracarboxylic dianhydride (NTDA) with p-aminophenol. A series of ternary copolymers derived from NTDA–OH were further synthesized by the nucleophilic substitution reactions. Both the monomer and the ternary copolymers were characterized by FT–IR, 1H NMR, and inductively coupled plasma (ICP). The characterization results showed that, the imide groups were successfully introduced into the prepared monomer. The differential scanning calorimetry (DSC) and the thermal gravimetry analysis (TGA) were further performed on the produced polymers. The thermal stability of the polymer increased with the content of the NTDA–OH increasing.